2020
DOI: 10.21203/rs.2.21019/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genome-wide identification of the 14-3-3 gene family and its participation in floral transition by interacting with TFL1/FT in Apple

Abstract: Background: Apple (Malus domestica Borkh.) is one of the most popular cultivated fruit crops in China. Apple floral transition is an important process but liable to be affected by various environmental factors. The 14-3-3 proteins are involved in regulating diverse biological processes in plants, and some 14-3-3 members play vital roles in flowering. However, little information was available about the 14-3-3 members in apple.Results: In the current study, we identified eighteen 14-3-3 gene family members from … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 68 publications
(122 reference statements)
1
1
0
Order By: Relevance
“…Phylogenetic analysis of 89 14-3-3 proteins belonging to wheat and six other plant species showed that these proteins were clustered into two major groups (ε and non-ε), which is consistent with previous reports [ 18 , 34 ]. The result indicates that the formation of these two isoforms is a basic and ancient difference ( Figure 2 D).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Phylogenetic analysis of 89 14-3-3 proteins belonging to wheat and six other plant species showed that these proteins were clustered into two major groups (ε and non-ε), which is consistent with previous reports [ 18 , 34 ]. The result indicates that the formation of these two isoforms is a basic and ancient difference ( Figure 2 D).…”
Section: Discussionsupporting
confidence: 91%
“…14-3-3 genes are ubiquitous in many species, and the study of its gene function is very necessary. Recent studies have shown that the four 14-3-3 proteins (MdGF14a, MdGF14d, MdGF14i, and MdGF14j) of apples interact with the flower integrator TFL1/FT and participate in flowering regulation [ 34 ]. Under the condition of nitrate deficiency, the interaction of MdGRF11 and MdBT2 in apples can induce the accumulation of anthocyanins and provide a new mechanism for anthocyanin biosynthesis [ 35 ].…”
Section: Discussionmentioning
confidence: 99%